Profesor Hanna Tadeusiewicz jako redaktor „Słownika pracowników książki polskiej” - Rzadkowolska, Magdalena; Walczak-Niewiadomska, Agata (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The article presents the imput of prof HannaTadeusiewicz’s work on “The Dictionary of Polish Book Labourers”. Since 1965 she was closely associated with this project, at first working in the Library of the University of Lodz, later in the Chair of the Library and Information Science at the University of Lodz. The paper focuses on prof. Hanna Tadeusiewicz’s impact on every volume carried out up to now and the subjective literature created by her during over 40 years.